Dramaturgi: Sebuah Pertunjukkan Panggung Depan Kehidupan Sosial Para Pelaku Awe-Awe Jalur Gumitir, Kabupaten Jember (Jurnal Insan Pendidikan dan Sosial Humaniora, 2023)
The social phenomenon of awe-awe actors that occurs on the Gumitir route, Garahan Village, Jember Regency. Along the edge of the Gumitir lane, there is a group of residents known as "Awe-awe" who initially had a role to help road users by providing signals and directions. But over time, they switched roles to become beggars, reflecting significant social change. The researcher found that the behavior carried out by the Awe-awe actors is a reflection of the Dramaturgy theory proposed by Erving Goffman. In their daily lives, awe-awe actors have a role that they play on the front stage. While on the other hand, they also hide their real life on the backstage. This research reveals the complexity of their social life, the reasons they choose this job due to economic limitations, and how they use various strategies to maintain the role of beggars. The research method used is qualitative with an ethnographic approach, using observation, interviews, and documentation. The results of the study provide insight into the social interactions of Awe-awe actors on the front stage and back stage of their lives.